Sport policy systems and sport federations (Palgrave Macmillan, 2017)
This book explores the organisation and structure of sport in and beyond Europe. Drawing upon up-to-date data, the collection`s main focus lies on the relationship between public sport policy structures and sport (con)federations. The authors present thirteen country-specific contexts wherein sport policy systems are embedded. This evidence provides in-depth descriptions and analyses within a solid academic and theoretical framework. This volume will be of interest to students and scholars of Sociology of Sport, Sport Management and Sport Policy.